Measuring Lymphocyte Proliferation in Response to Specific Antigen and Mitogen Stimuli Using Flow Cytometry - Heider, Stefan; Strobel, Joachim; Mempel, Wolfgang; Eckstein, Reinhold; Weisbach, Volker Günter (Clinical Laboratory, 2016)
BACKGROUND: We present a multivariate test system using flow cytometry after in-vitro lymphocyte stimulation using 5 mitogens and 7 antigens to describe in-vitro immunofunction. METHODS: The present work is a crucial step towards establishing a simple, CFSE-based, multivariate test system that can describe the dynamics of stimulus-induced lymphocyte proliferation with considerably more precision than is possible with the radionucleotide method using 3H-thymidine. Using multicolour flow cytometry, our method allows additional phenotyping of the proliferating cells and quantifies the proliferation behaviour by precisely resolving daughter generations and determining the precursor frequency. CONCLUSIONS: Taking the calculated apoptosis parameters into account not only provides additional information about the stimulus-specific response behaviour but also improves the validity of the commonly used proliferation indices. Not only can we confirm previous findings that healthy people have marked differences in a multivariate test system in terms of the individual in-vitro reactivity to various stimuli but also substantiate that the response pattern of an individual is remarkably constant. In follow-up studies we can show for the first time that the results of immunofunctional testing do not change over a period of at least 6 months and appear to be an inherent characteristic of the individual and thus possibly have a genetic basis.
EVALuna2:32777